A Comparative Analysis of Translesion DNA Synthesis Catalyzed by a High-Fidelity DNA Polymerase. Issue 15 (21st July 2017) - Dasari, Anvesh; Deodhar, Tejal; Berdis, Anthony J.
Abstract: Translesion DNA synthesis (TLS) is the ability of DNA polymerases to incorporate nucleotides opposite and beyond damaged DNA. TLS activity is an important risk factor for the initiation and progression of genetic diseases such as cancer. In this study, we evaluate the ability of a high-fidelity DNA polymerase to perform TLS with 8-oxo-guanine (8-oxo-G), a highly pro-mutagenic DNA lesion formed by reactive oxygen species. Results of kinetic studies monitoring the incorporation of modified nucleotide analogs demonstrate that the binding affinity of the incoming dNTP is controlled by the overall hydrophobicity of the nucleobase. However, the rate constant for the polymerization step is regulated by hydrogen-bonding interactions made between the incoming nucleotide with 8-oxo-G. Results generated here for replicating the miscoding 8-oxo-G are compared to those published for the replication of the non-instructional abasic site. During the replication of both lesions, binding of the nucleotide substrate is controlled by energetics associated with nucleobase desolvation, whereas the rate constant for the polymerization step is influenced by the physical nature of the DNA lesion, that is, miscoding versus non-instructional. Collectively, these studies highlight the importance of nucleobase desolvation as a key physical feature that enhances the misreplication of structurally diverse DNA lesions. Graphical Abstract: Highlights: Examines how a high-fidelity DNA polymerase misreplicates a miscoding DNA lesion Kinetic studies were performed using modified and artificial nucleotide analogs. Results show that high-fidelity DNA polymerases use nucleobase desolvation for binding. Demonstrates a role for nucleobase solvation in maintaining polymerase fidelity